Scientific and Legal Aspect for Conducting of Operational Measures to Counter Threats of Terrorist Acts upon Their Commission as a Challenge to the Social Community - NALUTSYSHYN, Viktor V.; YURCHYSHYN, Vasyl M.; CHEREPUSHCHAK, Vasyl V. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019DO - 10.14505/jarle.v10.7(45).17, 2019)
Terrorist threat act may lie not only in potential civilian casualties, but also in the investigation of acts that could in the long run lead to the implementation of terrorist intentions. The relevance of the study is determined by the fact that the possibility of preventing a terrorist act should be in the interdepartmental jurisdiction of law enforcement agencies not only as a task of emergency response, but also as a task of direct monitoring. The novelty of the study is determined by the fact that the authors consider the aspect of the formation of countermeasures against a terrorist act on the basis of liquidating the foundation of its social response. The very process of preventing a terrorist act predominantly affects only measures to destroy terrorists and reduce the number of potential victims. The paper demonstrates that in addition to this postulate, it is worth considering the need for an additional reduction in social resonance, which acts as an incentive. Formation of counteraction by law enforcement agencies allows to reduce the significance of the terrorist impact on society. The practical significance of the study is determined by the fact that each of the participants in countering the terrorist act is also capable of operative activities, which can also additionally level the structure for implementing the provisions of anti-terrorism legislation.